Pengaruh Penerapan Nilai-Nilai Islam Pada Asuransi Mandiri Bank Syariah Mandiri Terhadap Tingkat Kesejahteraan Nasabah (Studi Pada Bank Syariah Mandiri Watampone) - Zulqifli Zulqifli; St Habibah St Habibah (Institut Agama Islam Negeri (IAIN) Bone, 2019)
This study discusses the Effect of Islamic Values in Bank Syariah Mandiri Mandiri Insurance on Customer Welfare Levels (Study at Bank Syariah Mandiri Watampone). This study aims to determine how the effect of Islamic Values Implementation on Bank Syariah Mandiri Mandiri Insurance on Customer Welfare Levels. The results of the analysis show that the application of Islamic values to Mandiri Insurance simultaneously has a significant effect (0.054 0.1) and the level of welfare of customers (0.393). Six other variables can encourage Mandiri Insurance to improve customer welfare. The six variables are Al-Hurriyah / Freedom (t = 1,713), Al-Musawah / Equation (t = 0,304), Al-'Adalah / Justice (t = 0,839), As-Sidqh / Honesty (t = 1,083), Al -Ridha / Willingness (t = 0.345), and Al-Kitabah / Written (t = 1.244) with the level of welfare of the customer. The result can be used as a reference to improve the welfare of Bank Mandiri Syariah customers in the Bone branch.